ChemInform Abstract: Visible Light‐Induced Photoeletrochemical and Antimicrobial Properties of Hierarchical CuBi2O4 by Facile Hydrothermal Synthesis. Issue 35 (August 2016) - Zhu, Lu; Basnet, Pradip; Larson, Steven R.; Jones, Les P.; Howe, Jane Y.; Tripp, Ralph A.; Zhao, Yiping
Abstract: Narrow bandgap semiconductor CuBi2 O4 microstructures (3D hierarchical microspheres, microflowers, 1D microrods and nanorods) are fabricated by varying the conditions in hydrothermal reaction of stoichiometric amounts of Cu(NO3 )2 and Bi(NO3 )3 by differently concentrated NaOH additions (autoclave, 100 °C, 24 h).